Advances in Bioinformatics and Computational Biology 5th Brazilian Symposium on Bioinformatics, BSB 2010, Rio de Janeiro, Brazil, August 31-September 3, 2010. Proceedings - Ferreira, Carlos E.; Miyano, Satoru.; Stadler, Peter F. (Lecture Notes in Computer Science, 2010)
This book constitutes the proceedings of the 5th Brazilian Symposium on Bioinformatics, BSB 2010, held in Rio de Janeiro, Brazil, in August/September 2010. The 5 full papers and 5 extended abstracts presented were carefully reviewed and selected for inclusion in the book. The topics of interest vary in many areas of Bioinformatics, including sequence analysis, motifs, and pattern matching; biomedical text mining; biological databases, data management, integration; biological data mining; structural, comparative, and functional genomics; protein structure, modeling and simulation; gene identification, and regulation; gene expression analysis; gene and protein interaction and networks; molecular docking; molecular evolution and phylogenetics; computational systems biology; computational proteomics; statistical analysis of molecular sequences; algorithms for problems in computational biology; as well as applications in molecular biology, biochemistry, genetics, and associated subjects.